2011
DOI: 10.1103/physrevb.84.174413
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic properties of CaMn7O12

Abstract: We report that CaMn7O12 is a new magnetic multiferroic material. The appearance of a ferroelectric polarization coinciding with the magnetic phase transition (∼ 90 K) suggests the presence of ferroelectricity induced by magnetism, further confirmed by its strong magnetoelectric response. With respect to other known magnetic multiferroics, CaMn7O12 displays attractive multiferroic properties, such as a high ferroelectric critical temperature and large polarization. More importantly, these results open a new ave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
178
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(200 citation statements)
references
References 35 publications
20
178
2
Order By: Relevance
“…Clear anomalies can be observed at the T N1 = 90 K and T N2 = 48 K magnetic phase transition temperatures, consistent with an earlier report on polycrystalline samples. 20 In contrast, no anomaly can be resolved near T o = 250 K. …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Clear anomalies can be observed at the T N1 = 90 K and T N2 = 48 K magnetic phase transition temperatures, consistent with an earlier report on polycrystalline samples. 20 In contrast, no anomaly can be resolved near T o = 250 K. …”
Section: Resultsmentioning
confidence: 98%
“…1) prop- agating along the crystallographic c-axis. CaMn 7 O 12 exhibits multiferroic properties below T N1 = 90 K. An unprecedentedly large magnetically induced ferroelectric polarization [20][21][22] arises from a helical magnetic structure due to exchange striction, 22 and it is suggested that the orbital order at higher temperature sets the stage for the helical magnetic structure to be stabilized. 17 These novelties motivated us to study the mechanism for the orbital ordering in CaMn 7 O 12 using Raman spectroscopy, which is sensitive to symmetry breaking via the observation of collective excitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of polycrystalline samples showed that the development of long-range antiferromagnetic order below T N1 coincides with the onset of a large ferroelectric polarization [7]. In the present study, the electric polarization was measured on our single crystals perpendicular to the natural facets (parallel to the <100> pseudo-cubic axes) and along the three-fold axis of the rhombohedral cell, as shown in Fig.…”
mentioning
confidence: 99%
“…Here, we determine the origin of the magnetically induced ferroelectricity in CaMn 7 O 12 [7] through the analysis of electric polarization, magnetic susceptibility, and neutron powder diffraction measurements. We show that the magnetically induced polarization, the largest measured to date in any compound, develops at 90 K, oriented parallel to the c axis.…”
mentioning
confidence: 99%